To Assess the Beneficial Effects of Rosuvastatin Before Percutaneous Coronary Intervention in Patients with Acute Coronary Syndrome (Medical Forum Monthly, 2024)
Objective: To assess the frequency of major adverse cardiovascular events in patients who receive high dose Rosuvastatin before PCI. Study Design: Case series study. Place and Duration of Study: This study was conducted at the department of cardiology, Liaquat National Hospital & Medical College, Karachi from March 2018 to April 2019. Materials and Methods: During the period of study total number of ACS patients for percutaneous coronary intervention at Liaquat national hospital in the department of cardiology in which 271 patients were admitted and samples of 153 patients were taken by Non probability consecutive sampling. Results: The frequency of periprocedural myocardial injury/non fatal MI in patients who receive high dose Rosuvastatin before percutaneus coronary intervention is 6.5%, ECG changes after procedure that is development of pathological Q-wave found in 1.3% and sudden death in 0.7%. Conclusion: The use of single high loading dose of rosuvastatin is not only helpful to reduce periprocedural myocardial injury but also decreases other major adverse cardiac events such as development of pathological Qwave, non fatal myocardial infarction but no effect on prevention of sudden death.